2004
DOI: 10.1159/000081764
|View full text |Cite
|
Sign up to set email alerts
|

BALF Nitrite as an Indicator of Inflammation in Children with Cystic Fibrosis

Abstract: Background: A unique substance reflecting the degree of inflammation localized to the lower respiratory tract in patients with cystic fibrosis (CF) has been the concern of several investigators and nitric oxide has gained interest for this purpose in the last decades. Objectives: The aim of this study was to evaluate the cytokine and nitrite levels by showing the relationship between them in serum and bronchoalveolar lavage fluid (BALF) of patients with CF and patients in which flexible fiberoptic bronchoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…In another study, significant positive correlation was reported between BAL IL-8 and nitrite levels. 32 These results also confirm our findings supporting the idea of a low inflammatory situation caused by NAC treatment.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, significant positive correlation was reported between BAL IL-8 and nitrite levels. 32 These results also confirm our findings supporting the idea of a low inflammatory situation caused by NAC treatment.…”
Section: Discussionsupporting
confidence: 90%
“…24 The measurement of nitrite in breath condensates and BAL has been reported to objectively assess airway inflammation in asthmatic children and in cystic fibrosis and lung transplant recipients. [25][26][27][28] There was a significant positive correlation found between BAL IL-8 and nitrite levels. 27 These results also support our findings.…”
Section: Discussionmentioning
confidence: 81%
“…[25][26][27][28] There was a significant positive correlation found between BAL IL-8 and nitrite levels. 27 These results also support our findings. BAL nitrite concentration after 3 hours of warm ischemia was significantly higher in saline compared with Perfadex.…”
Section: Discussionmentioning
confidence: 81%
“…Bronchoscopy has been used for studying inflammatory markers such as Interleukin -8 and nitrite in the lower airway of patients with Cystic Fibrosis (Noah, T.L. 2003, Cetin, I. 2004, Davis, S.D.…”
Section: Role Of Bronchoscopy In Cystic Fibrosismentioning
confidence: 99%
“…There were no significant differences in the secondary outcomes such as FEV1, weight or BMI amongst the two groups. BAL fluid in cystic fibrosis patients has also been used to quantify and assess BAL fluid nitrite levels as this may reflect adequate the degree of inflammation in the respiratory tract and could potentially be a useful indicator of airway inflammation for patients with CF (Cetin, I 2004). …”
Section: Role Of Bronchoalveolar Lavage (Bal) In Bronchiectasis and Cfmentioning
confidence: 99%